UJI KARAKTERISTIK SPONGE IRON HASIL REDUKSI MENGGUNAKAN BURNER LAS ASITELIN DARI PASIR BESI PANTAI ASEMDOYONG PEMALANG - Yugo Pranoto; Sugeng Tirta Atmadja; Yusuf Umardhani (JURNAL TEKNIK MESIN, 2015)
Iron sand is sand deposits containing particles of iron ore (magnetite) found along the coast. Sponge iron is obtained from direct reduction of iron ore at a temperature below its melting point, using natural gas or gas reductant of coal or solid reductant such as coal. Sponge is also known as DRI (Directly reduced Iron) or substitute scrap (scrap substitute) in accordance with its function substitute scrap-iron in the steel industry. Sponge is some product manufacture of steel through a direct reduction process, the steel-making process flow of sponge through the burner welding asitelin. In this study is made of sponge iron from iron sand beaches raw materials Asemdoyong, Pemalang. This process uses the raw material composite pellets are made from a mixture of fine iron ore, coal, slag-forming materials and adhesives. From sampling 15 kg of sand, iron sand obtained 3.5634 kg, the percentage 23.75%. Sieving 100 mesh, obtained 2.3630 kg, the percentage of 15.75%. Briquettes are made as much as 3 kg, with a composition of 75% iron sand as 2.25 kg, 20% charcoal as much as 0.6 kg, and aci 5% as much as 0.15 kg. Briquettes produced weighing 44.47 grams per briquette. Carbon is used charcoal which serves as a reductant. Reduction of welding burner asitelin obtained sponge iron with varying weight, 12.16 g, 15.15 g and 16.61 g. Results of testing the composition of the AAS method, the composition of the raw materials obtained 52.12% Fe, 8.10% C, 1.94% Si, and 2.18% Mg. While the sponge iron is composed of 62.46% Fe, 2.70% C, 0.85% Si, and 1.43% Mg. From the data shown a significant increase in Fe content of 10.34%, and is accompanied by a decrease in the levels of impurities in the iron sand.